Risky research? Exploring the potentially detrimental effects of employing stigma scales - Ort, Alexander; Sukalla, Freya (Frontiers in Communication, 2023)
Research on stigma is confronted with major ethical challenges. One potential risk of investigating stigma utilizing self-reports includes the unintentional reinforcement of stigma. Commonly used self-report scales to assess stigma usually include items that directly confront people with the negative stereotypes underlying the stigma. Even though findings in the domain of priming research suggest that such a way of assessing stigma might potentially activate and reinforce existing stigma-relevant beliefs, research to date has neglected the issue of potential detrimental effects. A preregistered online experiment was conducted with a sample of 762 participants (51.1% female, age: M = 49.7 years, SD = 16.4, 69.9% with some form of tertiary education). The objective of the study was to explore the potential impact of exposure to stigma scales which incorporate negative stereotypes on the development of stigmatizing attitudes towards two specific groups: individuals who use pre-exposure prophylaxis for HIV prevention and patients who undergo weight loss surgery. The findings underline the relevance of the issue by showing that responding to negative stereotypical items on a stigma scale bears the risk of facilitating scale-related stereotype accessibility, negative judgment, and promoting social demarcation from the groups under investigation.